(untitled) (Update Dental College Journal, 2014)
The aim of this report is to discuss a case about a traumatized upper left central incisor presented with chronic periapical pathology with unusual presentation. In this case, the apical area of the tooth was exposed for a long period and the apex was open due to loss of affected tooth materials and its surrounding bone and soft tissue loss. The apical area was corrected with apical curettage and retrograde filling with Mineral Trioxide Aggregate (MTA) as well as soft tissue managed with pedicle flap design. The discolouration and mild shortening of the crown due to intrusive effect was managed by lamination of cosmetic restorative material. After 12 months follow up, the offending tooth was accepted both functionally and aesthetically. DOI: http://dx.doi.org/10.3329/updcj.v3i2.17998 Update Dent. Coll. j: 2013; 3 (2): 39-42